Metamaterials for Remote Generation of Spatially Controllable Two Dimensional Array of Microplasma - Singh, Pramod K. (Nature Publishing Group, 2014)
Since the initial demonstration of negative refraction and cloaking using metamaterials, there has been enormous interest and progress in making practical devices based on metamaterials such as electrically small antennas, absorbers, modulators, detectors etc that span over a wide range of electromagnetic spectrum covering microwave, terahertz, infrared (IR) and optical wavelengths. We present metamaterial as an active substrate where each unit cell serves as an element for generation of plasma, the fourth state of matter. Sub-wavelength localization of incident electromagnetic wave energy, one of the most interesting properties of metamaterials is employed here for generating high electric field to ignite and sustain microscale plasmas. Frequency selective nature of the metamaterial unit cells make it possible to generate spatially localized microplasma in a large array using multiple resonators. A dual resonator topology is shown for the demonstration. Since microwave energy couples to the metamaterial through free space, the proposed approach is naturally wireless. Such spatially controllable microplasma arrays provide a fundamentally new material system for future investigations in novel applications, e.g. nonlinear metamaterials.